#### Answer

$y=\sqrt[3]{x-1}$

#### Work Step by Step

We begin with:
$f(x)=\sqrt[3]{x}$
Shifting right 1 unit means $y=f(x-1)$. Thus we get:
$y=\sqrt[3]{x-1}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$y=\sqrt[3]{x-1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.